2016
DOI: 10.3892/ol.2016.5343
|View full text |Cite
|
Sign up to set email alerts
|

KIAA1377 is associated with lymph node metastasis in esophageal squamous cell carcinoma

Abstract: Abstract. KIAA1377, of which there are few studies regarding cell biology and neurological diseases, has been found to be significantly amplified in esophageal squamous cell carcinoma (ESCC) with lymph node metastasis compared with ESCC without lymph node metastasis. This suggests that KIAA1377 may play a role in the lymph node metastasis of ESCC. There has, to the best of our knowledge, been no study performed to investigate the role of KIAA1377 in ESCC. In the present study, the expression of KIAA1377 was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Nevertheless, the few reports (Chen et al, ; Bonavita et al, ) available exhibited that KIAA1377 takes part in the cytokinesis, cilium formation, microtubule, and mitotic spindle organization in normal cells. No evidence, however, has been reported concerning the biological role of KIAA1377 in cancer cells except of our own previous study performed in ESCC (Zheng et al, ), in which knock‐down of KIAA1377 mediated by transient transfection with short hairpin RNA (shRNA) inference showed that KIAA1377 seems to have no significant effect on the proliferation, migration, and invasion of ESCC cells. However, correlation analysis between KIAA1377 expression versus clinicopathological variables revealed that there was a significant correlation of KIAA1377 expression with lymph nodes metastases, which leads to the suggestion that KIAA1377 might be involved in the lymph node metastasis of ESCC cells.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, the few reports (Chen et al, ; Bonavita et al, ) available exhibited that KIAA1377 takes part in the cytokinesis, cilium formation, microtubule, and mitotic spindle organization in normal cells. No evidence, however, has been reported concerning the biological role of KIAA1377 in cancer cells except of our own previous study performed in ESCC (Zheng et al, ), in which knock‐down of KIAA1377 mediated by transient transfection with short hairpin RNA (shRNA) inference showed that KIAA1377 seems to have no significant effect on the proliferation, migration, and invasion of ESCC cells. However, correlation analysis between KIAA1377 expression versus clinicopathological variables revealed that there was a significant correlation of KIAA1377 expression with lymph nodes metastases, which leads to the suggestion that KIAA1377 might be involved in the lymph node metastasis of ESCC cells.…”
Section: Discussionmentioning
confidence: 87%
“…Factually, the role of KIAA1377 implicated in the setting of cancer has been little described, let alone in SCC. In our previous study, KIAA1377 was shown to be linked with lymph nodes metastases in ESCC (Zheng et al, 2016), hinting that KIAA1377 may be involved in the process. Despite this, the mechanism of regulation of KIAA1377 expression remains ill understood.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, the potential importance of KIAA genes in cancer is beginning to be recognized and studied, which has attracted considerable attention as a target for various biological events in tumorigenesis. A growing number of evidences have shown that abnormal expression of KIAA genes were associated with the development and prognosis of various cancers, such as gastric cancer, esophageal squamouscell carcinomas, colorectal cancer, lung cancer and breast cancer (12)(13)(14)(15)(16). Abnormal increase or loss of KIAA genes expression may contribute to tumor formation and development.…”
Section: Introductionmentioning
confidence: 99%
“…Low KIAA1324 expression was related to poor prognosis in patients with gastric cancer (12). KIAA1377 has been found to be significantly amplified in esophageal squamous cell carcinoma with lymph node metastasis (13). KIAA1199 has been identified as an oncogene in many cancers including breast cancer and associated with tumor invasion depth, TNM stage, and poor prognosis (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%